Thyrotoxicosis in Partial Mola Hidatidosa - Wedanta Mahadewi, I Gusti Agung; Purwa Sunu, Arya Baruna; Adisastra, Suryantha (International Journal of Advanced Multidisciplinary, 2024)
Thyrotoxicosis is a clinical condition associated with excessive thyroid hormone levels. Symptoms can range from asymptomatic to life-threatening due to thyroid storm. Thyrotoxicosis in hydatidiform moles is a rare condition but has a high mortality rate, so etiological studies are still needed for optimal management. Case Report: Patient Mrs. T, 25 years old Hindu, Balinese, 12 weeks pregnant (Gravida 1 Para 0 abortion 0), came to the obstetrics ER on September 24, 2023 with complaints of discharge from the birth canal since the morning, nausea (+), often shaking, easily tired and often sweaty. physical examination obtained blood pressure 100/60mmHg, pulse 78x/min, respiratory rate 20x/min, axillary temperature 36.80C oxygen saturation 99%. From obstetric examination, fundus uteri height ½ center, vaginal toucher vulva vagina within normal limits, portiono (-) fluxus (+), laboratory examination obtained HCG 387,392.8 mIU/m, FT4 31.05 pmol/L (N: 9-22), TSH <0.01 uIU/mL (N: 0.4-4.2) ultrasound results describe honey comb appearance and histopathology results describe partial mola.  Evacuation by curettage was performed, resulting in reduced serum ?-hCG levels and reduced thyroid hormone levels. Discussion: The patient was diagnosed with partial hydatidiform mole and thyrotoxicosis. Hydatidiform moles can cause thyrotoxicosis. This condition is caused by the structure of ?- hCG which resembles TSH so that it can activate TSH receptors.  After evacuation of hydatidiform moles, normal TSH and FT4 levels will be obtained. Conclusion: The female patient with thyrotoxicosis due to hydatidiform moles had the moles evacuated, resulting in normal thyroid hormone levels.